2015
DOI: 10.5894/rgci577
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the thermal effluent of a near coast power plant (Sines, Portugal)

Abstract: The present work is focused on the dispersion of a thermal effluent, produced by the Sines power plant, Portugal, along coastal waters. This facility intakes a yearly average around 40 m 3 /s of seawater, for the required cooling process, which is subsequently discharged back to the ocean at a 10 ºC increase in temperature. A three-dimensional hydrodynamic local model was nested into a regional model and set up to simulate the transport of the thermal effluent during two distinct periods, August and October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
1
8
1
Order By: Relevance
“…This causes the plume to rise faster, and therefore, it reaches the intake inlet with less dispersion. Similar behavior and results have been observed by other researchers and engineers [11,31,32]. …”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This causes the plume to rise faster, and therefore, it reaches the intake inlet with less dispersion. Similar behavior and results have been observed by other researchers and engineers [11,31,32]. …”
Section: Resultssupporting
confidence: 79%
“…The majority of such studies is focused on power plants located in coastal areas and not necessarily estuaries [5][6][7][8][9][10][11]. The work in [5] studied the outfall excess temperature for a 6000-MW nuclear power plant in coastal nearshore waters.…”
Section: Introductionmentioning
confidence: 99%
“…As the winds weaken, these mechanisms have more and more influence on the currents. Other existing studies [9] have shown the significant effects of the tide, which differs from the results observed for the present specific case study.…”
Section: Dcontrasting
confidence: 57%
“…The viability of numerical modeling is mainly due to both the progress in multidisciplinary modeling in recent decades and the progress in computing technologies and programming performance, which makes possible the computation of complex phenomena with high resolution and reduced processing times. Some recent works that study thermal plume dispersion, specifically from power plants, through numerical modeling can be consulted in [4] and [8,9]. This paper presents a study of a thermal plume dispersion into the sea caused by a power plant.…”
Section: Introductionmentioning
confidence: 99%
“…The horizontal dispersion of thermal plumes is mainly driven by wind-induced currents [He et al, 2006;Choi and Wilkin, 2007;Cardoso-Mohedano et al, 2015]. Near-shore regions close to the emitting source are therefore especially sensitive to thermal pollution since heat plumes can be trapped by coastal currents without being dispersed across the water body [Raithby et al, 1988;Salgueiro et al, 2015].…”
Section: Introductionmentioning
confidence: 99%